All‐pH Stable Sandwich‐Structured MoO2/MoS2/C Hollow Nanoreactors for Enhanced Electrochemical Hydrogen Evolution. (22nd April 2021) - Gong, Feilong; Liu, Mengmeng; Ye, Sheng; Gong, Lihua; Zeng, Guang; Xu, Lin; Zhang, Xiaoli; Zhang, Yonghui; Zhou, Liming; Fang, Shaoming; Liu, Jian
Abstract: Molybdenum sulfide has great potential for the electrocatalytic hydrogen evolution, but its structural instability in acidic media and high barriers in alkaline/neutral media limits its practical applications. Herein, the design of monodispersed sandwich‐structured MoO2 /MoS2 /C hollow nanoreactors is reported with a triple layer "conductor/catalyst/protector" configuration for efficient electrochemical hydrogen evolution over all pH values. Metallic MoO2 substrates with ultrahigh pristine electroconductivity can promote the charge transfer while sulfur vacancies are introduced to activate the highly exposed (002) facets of MoS2 . The optimized MoO2 /MoS2 /C nanoreactor exhibits overpotentials of 77, 91, and 97 mV (10 mA cm −2 ) and Tafel slopes of 41, 49, and 53 mV dec −1 in acidic, alkaline, and neutral media, respectively, which are much better than most of the MoS2 ‐based electrocatalysts. Moreover, defective carbon shells are in situ generated, preventing the electrocatalysts from corrosion in acidic and alkaline media; the structural stability is verified via in situ Raman and XRD characterizations. Based on the density functional theory calculations, vacancy engineering can regulate the band structures, electron density differences, total density of states, and the H* and H2 O adsorption‐dissociation ability over the entire pH range. The findings may shed light on the rational development of practical pH‐universal electrocatalysts for durable hydrogen evolution. Abstract : Monodispersed sandwich‐structured MoO2 /MoS2 /C hollow nanoreactors with "conductor/catalyst/protector" configuration are prepared. The metallic MoO2 substrate improves the charge transfer ability, sulfur vacancies activate the high‐energy (002) basal plane, and defective carbon prevents the catalysts from corrosion in acidic and alkaline media. The MoO2 /MoS2 /C nanoreactors present superior electrocatalytic hydrogen evolution activity and stability over all pH ranges.